Development of a 20 T 100 mm Cold Bore Superconducting Magnet System. (June 2020) - Ma, W; Hollis, T; Viznichenko, R; Twin, A; Clarke, N; Warren, D
Abstract: Oxford Instruments has successfully developed a series of large bore, high field magnet systems, using conventional NbTi and Nb3Sn low temperature superconductors (LTS). These magnet systems built to date have cold bores ranging from 150 mm to 250 mm diameter with central field from 15 T to 19 T. In this paper, we will introduce the development of a new member of high field and large bore magnet system at Oxford Instruments, with a central field of 20 T and cold bore of 100 mm. The magnet will be integrated with a special low-loss cryostat, generally stainless-steel construction with conductive radiation shields, constructed to minimize eddy currents and reinforced to withstand induced forces in the event of a magnet quench. The key technical challenges which must be met to provide such magnet system will be discussed in this paper.